The Application of Mandarin Industry Vocabulary Corpus Pages to Improve Translators Competence in the Industrial World - Nuratri, Ruth Kiana; Kusumaningtyas, Dani Putri Septi; Rahayu, Kristina Indah Setyo; Hasel, Clarosa Amanda; Sandyaningrum, Juairiah Nastiti (ABISATYA : Journal of Community Engagement, 2025)
The Mandarin language corpus has become an essential resource for enhancing translator competence, particularly amid the growing industrial cooperation between Indonesia and China. The availability of technical vocabulary sources remains limited, creating a gap between academic proficiency and the demands of professional translation in industry. This community service program aims to develop an online corpus of Mandarin industrial vocabulary as an effort to provide standardized terminology resources based on authentic data. The implementation methods include mapping user needs, collecting vocabulary from 30 undergraduate theses and student internship reports from 2021–2024, developing the digital platform, and conducting training on its use. A total of 4,221 vocabulary items were compiled and integrated into the corpus, equipped with search features based on hanzi, pinyin, and definitions. The results show that the corpus platform improves the accuracy of technical document translation, accelerates terminology retrieval, and strengthens both thematic and instrumental competencies of translators. This digital corpus has proven effective in supporting translation needs in academic and industrial settings.